Multicenter comparison of Etest, Vitek2 and BD Phoenix to broth microdilution for beta-lactam susceptibility testing of Streptococcus pneumonia - Steven Martens; Lize Cuypers; Florian Bélik; Pieter-Jan Briers; Pieter-Jan Ceyssens; Olivier Denis; Te-Din Huang; Koen Magerman; Thomas Strypens; Anne-Marie Van den Abeele; Stefanie Desmet (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose To assess performance of Etest®, Vitek®2 and BD Phoenix™ to determine the susceptibility of Streptococcus pneumoniae strains to penicillin, ampicillin and cefotaxime. Methods Sixty unique S. pneumoniae challenge strains were selected to cover a wide range of penicillin, ampicillin and cefotaxime minimal inhibitory concentrations (MICs). Strains were analyzed in four different Belgian laboratories. Etest® benzylpenicillin (BEN), ampicillin/amoxicillin (AMP) and cefotaxime (CTA) (bioMérieux), Vitek®2 AST-ST03 (bioMérieux) and BD Phoenix™ SMIC/ID-11 testing were each performed in two different labs. Results were compared to Sensititre® broth microdilution (BMD) (Thermo Fisher Scientific) results. MIC results were interpreted using EUCAST non-meningitis breakpoints (v 13.0). Results Essential agreement (EA) was ≥ 90% for all methods compared to BMD, except for Etest® BEN on Oxoid plate (58.3%), Etest® AMP (both on Oxoid (65.8%) and BD BBL plate (84.2%)). Categorical agreement (CA) for penicillin was only ≥ 90% for Vitek®2, for other methods CA ranged between 74 and 84%. CA for AMP was for all methods < 90% (range 75.8–88.3%) and CA for CTA was between 87 and 90% for all methods except for Etest on Oxoid plate (79.2%). Conclusions Our study indicates that Vitek®2 and BD Phoenix™ are reliable for providing accurate pneumococcal susceptibility results for BEN, AMP and CTA. Using Etest BEN or AMP on Oxoid plate carries a risk of underestimating the MIC and should be interpreted with caution, especially when the obtained MIC is 1 or 2 doubling dilutions below the S or R clinical breakpoint.

Multicenter interlaboratory study of routine systems for the susceptibility testing of temocillin using a challenge panel of multidrug-resistant strains - Corentin Deckers; Florian Bélik; Olivier Denis; Isabel Montesinos; Pierre Bogaerts; Jerina Boelens; Laetitia Brassinne; Julie Descy; Stefanie Desmet; Sarah Gils; Bénédicte Lissoir; Koen Magerman; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Infections at the nexus of metabolic-associated fatty liver disease - Joost Boeckmans; Matthias Rombaut; Thomas Demuyser; Baptist Declerck; Denis Piérard; Vera Rogiers; Joery De Kock; Luc Waumans; Koen Magerman; Reinoud Cartuyvels; Jean-Luc Rummens; Robim M. Rodrigues; et al. (Archives of Toxicology, 2021)

Multicenter study of automated systems for colistin susceptibility testing - Ahalieyah Anantharajah; Youri Glupczynski; Martin Hoebeke; Pierre Bogaerts; Philippe Declercq; Olivier Denis; Julie Descy; Katelijne Floré; Koen Magerman; Hector Rodriguez-Villalobos; Anne-Marie Van den Abeele; Te-Din Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2021)